Study of Some Patterns for Severe Rainfalls Over Iraq - Yaser Ali Shaghati (Mustansiriyah Journal of Science, 2020)
Study of rain received particularly great importance in the areas described as semi-arid, which is on the other hand are not well prepared for the drainage of rain that may turned into flash floods. The pressure systems, especially those passing through the country in the winter rainy season and spring also autumn have a role in determining the amount of rainfall falling in the region In addition to climate change and its effects in terms of climate cycles and climate extremes and thus required determine the size of rainfall Whether it is beneficial or harmful. In this study to determine of heavy rainfalls, two important cases of heavy rainfalls were studied in 24, Dec, 2016 and 24, Nov, 2018, which exceeded 50 mm on the Iraq, from one country to another in this account , rainfalls rate, divider from the World Meteorological Organization (WMO) in which the rain intensity is determined according to the schedule and limits (light precipitation I≤2 mm / hour), (moderate precipitation 2<I≤10 mm / Hour), (heavy precipitation 10 <I≤50 mm / hour), (torrential precipitation I> 50 mm / hour). Each case was Analyzed and visualized by using the data analysis and display system (GrADS) The data were obtained from Tropical Rainfall Measuring Mission (TRMM). Show maps results of the first case in (24 December, 2016) in the northeastern region, the central region and the western region of the country the abundant rain condition through maps of rainfall rates on these areas as well as by maps of mean sea level pressure and dense cloud cover, maps showed a decrease the temperature accompanying the low pressure also streamlines, geopotential height, relative vorticity show this. And show the vertical velocity (omega), relative humidity, geopotential height, relative vorticity, and show support of air decline in terms of streamlines, relative humidity, geopotential height and relative vorticity over the country. Maps 700 hPa the vertical velocity (omega), relative humidity, geopotential height and relative vorticity, maps 500 hPa, results of second case, (24 November, 2018) that occurred in the northeastern and eastern part and southeastern part of the country, also appear clear through maps of falling rainfall rates, as well as maps of sea level pressure and the dense cloud cover accompanying the heavy rain situation. maps 850 hPa it shows the low temperature accompanying the atmospheric decline, also streamlines, geopotential height and relative vorticity also maps 700 hPa and 500 hPa lik first case, in differential patterns all of this shows clear support for the atmospheric decline in terms of streamlines, relative humidity, geopotential height, and relative vorticity, and explain the causes of heavy rain situation over Iraq.